2019
DOI: 10.3390/molecules25010104
|View full text |Cite
|
Sign up to set email alerts
|

Reaction-Based Amine and Alcohol Gases Detection with Triazine Ionic Liquid Materials

Abstract: We demonstrated in this work the use of affinity ionic liquids, AIL 1 and AIL 2, for chemoselective detection of amine and alcohol gases on a quartz crystal microbalance (QCM). These detections of gaseous amines and alcohols were achieved by nucleophilic aromatic substitution reactions with the electrophilic 1,3,5-triazine-based AIL 1 thin-coated on quartz chips. Starting with inexpensive reagents, bicyclic imidazolium ionic liquids AIL 1 and AIL 2 were readily synthesized in six and four synthetic steps with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…With thirteen final ionic products ( IL 2 , ZIL 3a–f and ZIL 4a–f ) synthesized in this work, only ZIL 3a is an ionic salt with m.p. at 100 °C; other twelve are supercooled ionic liquids at room temperature [ 15 , 16 ] and viscous colorless-to-pale yellow liquid when obtained. As unambiguously demonstrated in Figure 3 , we were pleased that IL 2 not only was found as a room-temperature ionic liquid exhibiting UCST phase transition in water but also carried much lower T c value than that of IL 1 : 13 °C and 72 °C at 1:1 mass ratio, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With thirteen final ionic products ( IL 2 , ZIL 3a–f and ZIL 4a–f ) synthesized in this work, only ZIL 3a is an ionic salt with m.p. at 100 °C; other twelve are supercooled ionic liquids at room temperature [ 15 , 16 ] and viscous colorless-to-pale yellow liquid when obtained. As unambiguously demonstrated in Figure 3 , we were pleased that IL 2 not only was found as a room-temperature ionic liquid exhibiting UCST phase transition in water but also carried much lower T c value than that of IL 1 : 13 °C and 72 °C at 1:1 mass ratio, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sensing strategies for a variety of systems, from biological targets [158], environmental and regulatory applications [159,160], mechanical integrity of structures [161][162][163], and more [60,164], are continuously under investigation in the scientific community. In general, recognition can be categorized into two different methodologies: targeted and non-targeted [165].…”
Section: Sensing Materialsmentioning
confidence: 99%
“…The ionic liquids that we discussed above show reversible response, meaning that the analytes can be easily desorbed by blowing an inert gas [37]. There are several attempts to develop QCM sensors using specific chemical reactions of ILs with analytes, which can significantly increase the sensitivity and selectivity for several organic vapors; and, this type of ILs has been referred to as 'sensing ionic liquids' (SILs) [87][88][89][90][91][92][93]. Tseng and Chu [87] synthesized three SILs and used them for highly sensitive and selective detection of aldehyde, ketones, and amines.…”
Section: Reaction-based Sensing Ionic Liquids For Qcm Sensorsmentioning
confidence: 99%
“…Hsu et al [92] reported the detection of alkenes gas through the use of Diels-Alder [4+2] cycloaddition reaction of alkenes with so-called functional ionic liquids, and the sensitivity of detection was reported to be 1.5 ppb for cyclopentadiene. Li and Chu [93] reported detection of alcohol and amine gases by utilizing triazine-based ILs and nucleophilic aromatic substitution reactions. These reaction-based IL systems provide high sensitivity, high selectivity, and no sensitivity to moisture as compared to the ILs discussed in Section 4.1.…”
Section: Reaction-based Sensing Ionic Liquids For Qcm Sensorsmentioning
confidence: 99%